DIAGNOSTICS OF INDUCTION MOTOR ROTOR COMBINED DEFECTS WITH AN INDUCTION METHOD - Y.N. Vas’kovsky; M.A. Kovalenko (Electrical engineering & Electromechanics, 2013)
A diagnostics methodology for combined defects of induction motor rotors is introduced, the defects considered being simultaneous damage of rods, cage rings, and the rotor active steel. Diagnostic features and recommendations on the rotor combined defects identification are formulated.